Experimental Study to the Effect of Natural Particles Added to Unsaturated Polyester Resin of a Polymer Matrix Composite - Abdullah, Orhan S. (Al-Khwarizmi Engineering Journal, 2017)
Experimental investigations had been done in this study to demonstrate the effect of natural particles used as a reinforcement material to unsaturated polyester resin. The tensile test and water absorption were investigated according to (ASTM D638) and (ASTM D570), respectively. The influence of sunflower husk and pomegranate husk particles, used as a reinforcement material, on the tensile strength, Young's modulus and water absorption with different weight fraction (3%, 7% and 10%) and particle grain size (50µm, 100 µm and 150 µm), has been investigated. The water absorption of polymer composites was studied by measuring the specimen weight before and after immersion in water for one hundred days. In the experiments of tensile test, all specimens loading was performed with (50KN) operating at a crosshead speed of 10 mm/min. It is observed that the addition of sunflower husk up to 10% and pomegranate husk particles up to 7% as reinforcement materials to polyester resin, leads to increase the tensile strength and Young's modulus of the composite material prepared and the use of sunflower husk as a reinforcement material increased the tensile strength, Young's modulus and water absorption were better  than pomegranate husk at the same percentage of addition. The decrease in reinforcement material grain size led to increase the tensile strength, Young's modulus and water absorption. Therefore, all the best result seen in composites containing reinforcement material with (50µm). Finally, the best result obtained in tensile strength, Young's modulus and water absorption were with the addition of 10% sunflower husk as a reinforcement material to polyester resin.